Vada-Tarka Vidya is a means of improving the intellectual abilities of Hindu students - Wariati, Ni Luh Gede; Listyaantari (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Introduction: Dialogue, discussion and debate are nothing new in the Hindu tradition. Smart people must master a variety of communication techniques, including discussion and debate. The importance of the art of dialogue and opening oneself to various points of view in the search for truth. Although derived from the past, Tarka Vada's insights remain relevant in the modern context Methods: This research is a type of research that uses qualitative methods by conducting literature reviews, and online data searches as data collection techniques. The purpose of using this method is to collect as much information as possible. Finding: Tarka Vidya and Vada Vidya in vada as a means of increasing the intellectual abilities of Hindu students. It can guide thinking towards a deeper and purposeful understanding in the Hindu intellectual environment.